Internal-external cross-validation helped to evaluate the generalizability of prediction models in large clustered datasets - Takada, Toshihiko; Nijman, Steven; Denaxas, Spiros; Snell, Kym I.E.; Uijl, Alicia; Nguyen, Tri-Long; Asselbergs, Folkert W.; Debray, Thomas P.A. (JOURNAL OF CLINICAL EPIDEMIOLOGY, 2021)
To illustrate how to evaluate the need of complex strategies for developing generalizable prediction models in large clustered datasets. We developed eight Cox regression models to estimate the risk of heart failure using a large population-level dataset. These models differed in the number of predictors, the functional form of the predictor effects (non-linear effects and interaction) and the estimation method (maximum likelihood and penalization). Internal-external cross-validation was used to evaluate the models’ generalizability across the included general practices. Among 871,687 individuals from 225 general practices, 43,987 (5.5%) developed heart failure during a median follow-up time of 5.8 years. For discrimination, the simplest prediction model yielded a good concordance statistic, which was not much improved by adopting complex strategies. Between-practice heterogeneity in discrimination was similar in all models. For calibration, the simplest model performed satisfactorily. Although accounting for non-linear effects and interaction slightly improved the calibration slope, it also led to more heterogeneity in the observed/expected ratio. Similar results were found in a second case study involving patients with stroke. In large clustered datasets, prediction model studies may adopt internal-external cross-validation to evaluate the generalizability of competing models, and to identify promising modelling strategies.